Population Growth and Healthcare Financing in Nigeria: Causality and Policy Implications - Pocho, Anthony Gabriel; Abutu, Leonard Akoh; Matudi, Inusa Utiwore; Ijighere, Clement Andrew (Cattleya Darmaya Fortuna, 2025)
Rising population comes with consequences, but we are concern about the health implications of this trend especially in regards to Nigeria, hence the need to interrogate population growth and healthcare financing in Nigeria: causality and policy implications, between year 2000 to 2022. Time series data were sourced from relevant organisations. The study explored the Auto Regressive Distributed lag model approach and Granger causality test for estimation. Outcome of the ARDL indicated that, the employment status of Nigerians citizens has noteworthy effect on healthcare financing in the future and population growth, educational expenditure and unemployment rate are all influential on healthcare financing in the interim. While the Granger causality test indicated a unidirectional causality between; population growth and healthcare financing, population growth and educational expenditure, unemployment rate and population growth, gross domestic product per capita and unemployment rate and a weak causality between unemployment rate and healthcare financing. While there was no causation between healthcare financing and gross domestic product per capita, educational expenditure and healthcare financing, educational expenditure and gross domestic product per capita, unemployment rate and healthcare financing and unemployment rate and educational expenditure. It is on this premise that the following suggestions where arrived at; budgetary allocation to the health and educational sector should be done in reflection to the rising population and that skills acquisition should go along with the educational curriculum to enhance the chances for economic mobility.